Radiotherapy patterns of care in gastric adenocarcinoma: a single institution experience - Cheng, Jessica; Squires III, Malcolm H.; Mikell, John L.; Fisher, Sarah B.; Staley III, Charles A.; Kooby, David A.; El-Rayes, Bassel F.; Curran Jr, Walter J.; Hall, William A.; Colbert, Lauren E.; Shelton, Joseph W.; Maithel, Shishir K.; et al. (Journal of Gastrointestinal Oncology; Vol 6, No 3 (June 01, 2015): Journal of Gastrointestinal Oncology, 2015)
Background: Gastric adenocarcinoma (GAC) is one of the most commonly diagnosed cancers worldwide. Two standard approaches for treatment of resectable GAC include adjuvant 5-fluorouracilbased chemoradiotherapy [per Intergroup 0116 (INT-0116) trial and perioperative epirubicin, cisplatin, fluorouracil (ECF) chemotherapy per Medical Research Council Adjuvant Gastric Infusional Chemotherapy (MAGIC) trial]. Controversy remains regarding the most appropriate treatment strategy to decrease recurrence rates and improve survival following surgery. The purpose of this study was to analyze how patterns of care for patients with GAC treated at Emory University Hospital changed following publication of the MAGIC trial in 2006. Methods: We analyzed a prospectively maintained database of 150 patients who underwent resection for GAC between December 2000 and June 2013. Patients were divided into two cohorts, Early [2000-2006] and Late [2007-2013]. The primary objective was to compare the number of patients assigned to adjuvant chemoradiotherapy (aCRT) vs. perioperative chemotherapy (PC) throughout the study period and secondarily assess for recurrence patterns and survival outcomes for patients assigned to those two strategies. Results: Between 2000 and 2013, 124 patients received adjuvant therapy for GAC. Fifty-four patients were treated with PC and 70 patients with aCRT. The early cohort included 56 patients, and the late cohort included 94 patients. There was no statistical difference in the number of patients receiving aCRT between the Early and Late cohorts [n=23 (50%) vs. 35 (38%) respectively, P=0.21]. PC increased from 2 patients (3.6%) in the Early cohort to 32 patients (34%) in the Late cohort (P